bikramphy

50 Reputation

2 Badges

0 years, 177 days

MaplePrimes Activity


These are questions asked by bikramphy

I am trying  to solve a first order differential equation.  But the maple is not able to solve. Please help me in finding the solutions...

Exact solution is not necessary. Solution in the series expansion is also be very helpful.

Here is the attached maple code..Please do check. Please scroll down to download the given maple file.


 

``

``

restart

with(Student[NumericalAnalysis])

with(PDEtools)

with(DEtools)

with(MmaTranslator)

[FromMma, FromMmaNotebook, Mma, MmaToMaple]

(1)

``

``

``

C1 := 2*M/(4*M*R^2*a-3*R^3*a)

``

D1 := -M*(8*M-9*R)*(3*ln(1+2*M/(4*M-3*R))+2*ln(1-2*M/R))/(3*R^2*(-16*M^2+26*M*R-9*R^2+(16*M^2-30*M*R+11*R^2)*ln(1+2*M/(4*M-3*R))+R^2*ln(-3*R/(4*M-3*R))))

``

A1 := R^2*(3*ln(1+2*M/(4*M-3*R))+2*ln(1-2*M/R))/(-32*M^2+52*M*R-18*R^2+(2*(16*M^2-30*M*R+11*R^2))*ln(1+2*M/(4*M-3*R))+2*R^2*ln(-3*R/(4*M-3*R)))

``

explambda := simplify((-2*C1*a*r^2+1)/(C1*a*r^2+1))

``

density := simplify(a*C1*(2*C1*a*r^2-3)/(-2*C1*a*r^2+1)^2)

``

pr := simplify(-D1+3*a*A1*C1*(2*C1*a*r^2-3)/(-2*C1*a*r^2+1)^2)

``

pt := simplify((D1*(-D1*r^2+4)-4*a^4*C1^4*r^6*(9*(1+A1)^2-(4*(1+3*A1))*D1*r^2+4*D1^2*r^4)+2*a*C1*(18*A1-(16+9*A1)*D1*r^2+4*D1^2*r^4)-3*a^2*C1^2*r^2*(9+16*A1+27*A1^2-(28*(1+A1))*D1*r^2+8*D1^2*r^4)+4*a^3*C1^3*r^4*(18+3*A1*(17+9*A1)-(10*(2+3*A1))*D1*r^2+8*D1^2*r^4))/((4*(C1*a*r^2+1))*(2*C1*a*r^2-1)^3))

``

drhodp := simplify(1/A1)

``

dptdp := (diff(pt, r))/(diff(pr, r))

``

A := simplify(-(-1-explambda)/r+4*explambda*Pi*r*(pr-density))

``

B := -(explambda^2+4*explambda+1)/r^2-64*explambda^2*Pi^2*r^2*pr^2-16*explambda*Pi*((-2+explambda)*pr-pt-density)-(-4*explambda*Pi*(pr+density)-4*explambda*Pi*drhodp*(pr+density))/dptdp

``

sys := {r*(diff(y(r), r))+y(r)^2+(A*r-1)*y(r)+r^2*B = 0}

 

[moderator edited to remove pages of output]
 

Download CALCULATION_OF_Y_v1.mw
 

I am trying to solve a differential equation numerically. But I am facing some difficulties. It is saying that ODE system has a removable singularity at r = 0. How can I remove the singularity?  Please check the attached figure and try to help.

Given a lagrangian  in general relativity , how can I calculate equation of motion using euler lagrangian equation in maple software ?

the lagrangian is 

L = 1/2 g[mu,nu] diff(x[~mu], lambda) diff(x[~nu],lambda)

here lambda is the affine parameter.  and the metric is 

 

 

metric coordinate = (t,u,x,y)

I want to series expand the HeunB function. But I am facing some problems with this. please help. Here is the given HeunB function. 

HB1 := HeunB(5/2, -5^(1/4)*(2*M - R)/sqrt((2*M - R)*(4*M - R)), (17*sqrt(5))/10, (3*5^(3/4)*(2*M - R))/(2*sqrt((2*M - R)*(4*M - R))), 5^(1/4)*sqrt((2*M - R)*(4*M - R))*r^2/(2*(2*M - R)*R^2))

 

Here M, R are arbitrary constants.

I want to to solve the system of partial differential equation using maple. I tried it but I am not able to solve it ... please help.

the equations are as follows

 


 

``

Finding transformation eqn between zero and harmonic with conformal1

``

 

restart

``

with(PDEtools)

sys := {(diff(Phi(r1, r2, r4), r1))^2-(diff(R(r1, r2, r4), r1))^2 = cos(T(r1, r2, r4))^2, (diff(Phi(r1, r2, r4), r2))^2-(diff(R(r1, r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, -(diff(R(r1, r2, r4), r2))*(diff(R(r1, r2, r4), r1))+(diff(Phi(r1, r2, r4), r2))*(diff(Phi(r1, r2, r4), r1)) = 0, -(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r1))+(diff(Theta(r1, r2, r4), r1))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1)) = 0, -(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2))+(diff(Theta(r1, r2, r4), r2))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2)) = 0, (R(r1, r2, r4)^2-Phi(r1, r2, r4)^2)*(diff(T(r1, r2, r4), r4))^2+2*(diff(Theta(r1, r2, r4), r4))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))^2-(diff(R(r1, r2, r4), r4))^2 = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2}

{(diff(Phi(r1, r2, r4), r1))^2-(diff(R(r1, r2, r4), r1))^2 = cos(T(r1, r2, r4))^2, (diff(Phi(r1, r2, r4), r2))^2-(diff(R(r1, r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, -(diff(R(r1, r2, r4), r2))*(diff(R(r1, r2, r4), r1))+(diff(Phi(r1, r2, r4), r2))*(diff(Phi(r1, r2, r4), r1)) = 0, -(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r1))+(diff(Theta(r1, r2, r4), r1))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1)) = 0, -(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2))+(diff(Theta(r1, r2, r4), r2))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2)) = 0, (R(r1, r2, r4)^2-Phi(r1, r2, r4)^2)*(diff(T(r1, r2, r4), r4))^2+2*(diff(Theta(r1, r2, r4), r4))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))^2-(diff(R(r1, r2, r4), r4))^2 = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2}

(1)

``

declare(Phi(r1, r2, r4), R(r1, r2, r4), T(r1, r2, r4), Theta(r1, r2, r4))

` Phi`(r1, r2, r4)*`will now be displayed as`*Phi

 

` R`(r1, r2, r4)*`will now be displayed as`*R

 

` T`(r1, r2, r4)*`will now be displayed as`*T

 

` Theta`(r1, r2, r4)*`will now be displayed as`*Theta

(2)

``

cases := [PDEtools:-casesplit({(diff(Phi(r1, r2, r4), r1))^2-(diff(R(r1, r2, r4), r1))^2 = cos(T(r1, r2, r4))^2, (diff(Phi(r1, r2, r4), r2))^2-(diff(R(r1, r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, -(diff(R(r1, r2, r4), r2))*(diff(R(r1, r2, r4), r1))+(diff(Phi(r1, r2, r4), r2))*(diff(Phi(r1, r2, r4), r1)) = 0, -(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r1))+(diff(Theta(r1, r2, r4), r1))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1)) = 0, -(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2))+(diff(Theta(r1, r2, r4), r2))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2)) = 0, (R(r1, r2, r4)^2-Phi(r1, r2, r4)^2)*(diff(T(r1, r2, r4), r4))^2+2*(diff(Theta(r1, r2, r4), r4))*(diff(T(r1, r2, r4), r4))+(diff(Phi(r1, r2, r4), r4))^2-(diff(R(r1, r2, r4), r4))^2 = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2}, caseplot)]

`========= Pivots Legend =========`

 

p1 = diff(R(r1, r2, r4), r2)

 

p2 = diff(Phi(r1, r2, r4), r1)

 

p3 = (diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^2

 

p4 = diff(Phi(r1, r2, r4), r2)

 

p5 = diff(R(r1, r2, r4), r1)

 

 

[`casesplit/ans`([diff(Theta(r1, r2, r4), r4) = (1/2)*(Phi(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-R(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-(diff(Phi(r1, r2, r4), r4))^2+(diff(R(r1, r2, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (-(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1))*(diff(Phi(r1, r2, r4), r2))^2-(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1))*cos(T(r1, r2, r4))^2+(diff(Phi(r1, r2, r4), r1))*(diff(Phi(r1, r2, r4), r2))*(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2)))/(cos(T(r1, r2, r4))^2*(diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^4), diff(Theta(r1, r2, r4), r2) = (-(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2))+(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2)))/cos(T(r1, r2, r4))^2, diff(diff(R(r1, r2, r4), r4), r4) = -R(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(R(r1, r2, r4), r4)), diff(R(r1, r2, r4), r1) = (diff(Phi(r1, r2, r4), r2))*(diff(Phi(r1, r2, r4), r1))/(diff(R(r1, r2, r4), r2)), (diff(R(r1, r2, r4), r2))^2 = (diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^2, diff(diff(Phi(r1, r2, r4), r4), r4) = -Phi(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(Phi(r1, r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), diff(diff(Phi(r1, r2, r4), r2), r4) = -(diff(Phi(r1, r2, r4), r2))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), diff(diff(Phi(r1, r2, r4), r2), r2) = 0, (diff(Phi(r1, r2, r4), r1))^2 = (diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0], [diff(R(r1, r2, r4), r2) <> 0, diff(Phi(r1, r2, r4), r1) <> 0]), `casesplit/ans`([diff(Theta(r1, r2, r4), r4) = (1/2)*(Phi(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-R(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-(diff(Phi(r1, r2, r4), r4))^2+(diff(R(r1, r2, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(R(r1, r2, r4), r4), r4) = -R(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(R(r1, r2, r4), r4)), diff(R(r1, r2, r4), r2) = 0, (diff(R(r1, r2, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(Phi(r1, r2, r4), r4), r4) = -Phi(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(Phi(r1, r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), diff(Phi(r1, r2, r4), r1) = 0, (diff(Phi(r1, r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0], [diff(R(r1, r2, r4), r1) <> 0, diff(Phi(r1, r2, r4), r2) <> 0])]

(3)

``

map(length, cases)

[2101, 1405]

(4)

sys1 := op(1, cases[2])

[diff(Theta(r1, r2, r4), r4) = (1/2)*(Phi(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-R(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-(diff(Phi(r1, r2, r4), r4))^2+(diff(R(r1, r2, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(R(r1, r2, r4), r4), r4) = -R(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(R(r1, r2, r4), r4)), diff(R(r1, r2, r4), r2) = 0, (diff(R(r1, r2, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(Phi(r1, r2, r4), r4), r4) = -Phi(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(Phi(r1, r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), diff(Phi(r1, r2, r4), r1) = 0, (diff(Phi(r1, r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0]

(5)

``

sys2 := op(1, cases[1])

[diff(Theta(r1, r2, r4), r4) = (1/2)*(Phi(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-R(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-(diff(Phi(r1, r2, r4), r4))^2+(diff(R(r1, r2, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (-(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1))*(diff(Phi(r1, r2, r4), r2))^2-(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r1))*cos(T(r1, r2, r4))^2+(diff(Phi(r1, r2, r4), r1))*(diff(Phi(r1, r2, r4), r2))*(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2)))/(cos(T(r1, r2, r4))^2*(diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^4), diff(Theta(r1, r2, r4), r2) = (-(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2))+(diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r2)))/cos(T(r1, r2, r4))^2, diff(diff(R(r1, r2, r4), r4), r4) = -R(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(R(r1, r2, r4), r4)), diff(R(r1, r2, r4), r1) = (diff(Phi(r1, r2, r4), r2))*(diff(Phi(r1, r2, r4), r1))/(diff(R(r1, r2, r4), r2)), (diff(R(r1, r2, r4), r2))^2 = (diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^2, diff(diff(Phi(r1, r2, r4), r4), r4) = -Phi(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(Phi(r1, r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), diff(diff(Phi(r1, r2, r4), r2), r4) = -(diff(Phi(r1, r2, r4), r2))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), diff(diff(Phi(r1, r2, r4), r2), r2) = 0, (diff(Phi(r1, r2, r4), r1))^2 = (diff(Phi(r1, r2, r4), r2))^2+cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0]

(6)

``

sys3 := op(2, cases[1])

[diff(R(r1, r2, r4), r2) <> 0, diff(Phi(r1, r2, r4), r1) <> 0]

(7)

``

sys4 := op(2, cases[2])

[diff(R(r1, r2, r4), r1) <> 0, diff(Phi(r1, r2, r4), r2) <> 0]

(8)

``

sol1 := dsolve(sys1, explicit)

(9)

``

constraint, subsystem := selectremove(has, sys1, T)

[diff(Theta(r1, r2, r4), r4) = (1/2)*(Phi(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-R(r1, r2, r4)^2*cos(T(r1, r2, r4))^4-(diff(Phi(r1, r2, r4), r4))^2+(diff(R(r1, r2, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(R(r1, r2, r4), r4))*(diff(R(r1, r2, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(Phi(r1, r2, r4), r4))*(diff(Phi(r1, r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(R(r1, r2, r4), r4), r4) = -R(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(R(r1, r2, r4), r4)), (diff(R(r1, r2, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(Phi(r1, r2, r4), r4), r4) = -Phi(r1, r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(Phi(r1, r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), (diff(Phi(r1, r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0], [diff(R(r1, r2, r4), r2) = 0, diff(Phi(r1, r2, r4), r1) = 0]

(10)

``

sol__subsystem := dsolve(subsystem)

{Phi(r1, r2, r4) = _F1(r2, r4), R(r1, r2, r4) = _F2(r1, r4)}

(11)

``

eval(constraint, sol__subsystem)

[diff(Theta(r1, r2, r4), r4) = (1/2)*(_F1(r2, r4)^2*cos(T(r1, r2, r4))^4-_F2(r1, r4)^2*cos(T(r1, r2, r4))^4-(diff(_F1(r2, r4), r4))^2+(diff(_F2(r1, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(_F2(r1, r4), r4))*(diff(_F2(r1, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(_F1(r2, r4), r4))*(diff(_F1(r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(_F2(r1, r4), r4), r4) = -_F2(r1, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(_F2(r1, r4), r4)), (diff(_F2(r1, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(_F1(r2, r4), r4), r4) = -_F1(r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(_F1(r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), (diff(_F1(r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0]

(12)

map(simplify, [diff(Theta(r1, r2, r4), r4) = (1/2)*(_F1(r2, r4)^2*cos(T(r1, r2, r4))^4-_F2(r1, r4)^2*cos(T(r1, r2, r4))^4-(diff(_F1(r2, r4), r4))^2+(diff(_F2(r1, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(_F2(r1, r4), r4))*(diff(_F2(r1, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(_F1(r2, r4), r4))*(diff(_F1(r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(_F2(r1, r4), r4), r4) = -_F2(r1, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(_F2(r1, r4), r4)), (diff(_F2(r1, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(_F1(r2, r4), r4), r4) = -_F1(r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(_F1(r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), (diff(_F1(r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0])

[diff(Theta(r1, r2, r4), r4) = (1/2)*((_F1(r2, r4)^2-_F2(r1, r4)^2)*cos(T(r1, r2, r4))^4-(diff(_F1(r2, r4), r4))^2+(diff(_F2(r1, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(_F2(r1, r4), r4))*(diff(_F2(r1, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(_F1(r2, r4), r4))*(diff(_F1(r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(_F2(r1, r4), r4), r4) = -cos(T(r1, r2, r4))*(_F2(r1, r4)*cos(T(r1, r2, r4))^3+2*(diff(_F2(r1, r4), r4))*sin(T(r1, r2, r4))), (diff(_F2(r1, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(_F1(r2, r4), r4), r4) = -cos(T(r1, r2, r4))*(_F1(r2, r4)*cos(T(r1, r2, r4))^3+2*(diff(_F1(r2, r4), r4))*sin(T(r1, r2, r4))), (diff(_F1(r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = sin(T(r1, r2, r4))^2, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0]

(13)

``

eval(constraint, sol__subsystem)

[diff(Theta(r1, r2, r4), r4) = (1/2)*(_F1(r2, r4)^2*cos(T(r1, r2, r4))^4-_F2(r1, r4)^2*cos(T(r1, r2, r4))^4-(diff(_F1(r2, r4), r4))^2+(diff(_F2(r1, r4), r4))^2)/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r1) = (diff(_F2(r1, r4), r4))*(diff(_F2(r1, r4), r1))/cos(T(r1, r2, r4))^2, diff(Theta(r1, r2, r4), r2) = -(diff(_F1(r2, r4), r4))*(diff(_F1(r2, r4), r2))/cos(T(r1, r2, r4))^2, diff(diff(_F2(r1, r4), r4), r4) = -_F2(r1, r4)*cos(T(r1, r2, r4))^4-2*cos(T(r1, r2, r4))*sin(T(r1, r2, r4))*(diff(_F2(r1, r4), r4)), (diff(_F2(r1, r4), r1))^2 = -cos(T(r1, r2, r4))^2, diff(diff(_F1(r2, r4), r4), r4) = -_F1(r2, r4)*cos(T(r1, r2, r4))^4-2*(diff(_F1(r2, r4), r4))*cos(T(r1, r2, r4))*sin(T(r1, r2, r4)), (diff(_F1(r2, r4), r2))^2 = -cos(T(r1, r2, r4))^2, sin(T(r1, r2, r4))^2 = -cos(T(r1, r2, r4))^2+1, diff(T(r1, r2, r4), r4) = cos(T(r1, r2, r4))^2, (diff(T(r1, r2, r4), r1))*sin(T(r1, r2, r4)) = 0, (diff(T(r1, r2, r4), r2))*sin(T(r1, r2, r4)) = 0, diff(T(r1, r2, r4), r1) = 0, diff(T(r1, r2, r4), r2) = 0]

(14)

``

``


 

Download Finding_transformation_eqn_between_zero_and_harmonic_with_conformal1.mw

1 2 Page 1 of 2